Association between obstructive sleep apnea and hyperuricemia/gout in the general population: a cross-sectional study - Suyeon Park; Seong-Hyeok Bak; Hyun-Sook Kim; Kyung-Ann Lee (BMC Musculoskeletal Disorders)
Abstract Background Obstructive sleep apnea (OSA) is linked to various health conditions, including cardiovascular diseases and metabolic disorders. Hyperuricemia and gout may be associated with OSA, but large-scale studies on this are limited. This study aimed to investigate the association between hyperuricemia/gout and OSA using data from the Korea National Health and Nutrition Survey (KNHANES). Methods Using the 2019–2021 KNHANES data, 11,728 participants were selected. OSA risk was assessed using the STOP-BANG questionnaire score, which is as follows: (1) high-risk (5–8), (2) intermediate-risk (3–4), and (3) low-risk (0–2). Anthropometric, socioeconomic, health-related variables, and biochemical measurements, including serum uric acid (SUA) levels, were included in the analysis. Multiple regression analyses examined the association between the STOP-BANG score and hyperuricemia/gout. Results After assigning weights, among 25,354,276 individuals, 3,114,119 (12.2%) had a high OSA risk. The high OSA risk group exhibited higher SUA levels (5.9 mg/dL) than those of the intermediate (5.6 mg/dL) and low OSA risk groups (4.7 mg/dL) (P < 0.001). Additionally, it had a higher incidence of physician-diagnosed gout than the other groups (6.6% vs. 3.8% vs. 0.8%, respectively, P < 0.001). The STOP-BANG questionnaire scores and SUA levels were positively correlated (r = 0.383; P < 0.001). When adjusted for confounding factors, the high OSA risk group demonstrated an association with hyperuricemia (SUA ≥ 6.8 mg/d) (adjusted Odds Ratio [OR]: 1.462, 95% Confidence interval [CI]: 1.108–1.929). High and intermediate OSA risk was associated with severe hyperuricemia (SUA ≥ 9.0 mg/dL) and gout; however, the significant association between OSA and severe hyperuricemia and gout attenuated to null after adjusting for confounding factors. Conclusions High OSA risk was independently associated with hyperuricemia but not severe hyperuricemia or gout. Screening and management of OSA may help prevent hyperuricemia.